CHARACTERISTICS OF INDIRECT EVIDENCE TOWARDS PRICE FIXING AGREEMENTS IN THE PERSPECTIVE OF COMPETITION LAW - Elreddian Kusuma Dewi; Zahry Vandawati Chumaida; Sinar Aju Wulandari (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
In the ever-changing landscape of Indonesian business, the pursuit of profits drives actors to engage in intense competition, all regulated by the Business Competition Law. This unique legal field combines both conventional law and economics to address unfair business practices, such as agreements that manipulate prices to deceive consumers. This research focuses on the characteristics of indirect evidence utilized by the Business Competition Supervisory Commission (KPPU) when investigating cases of price-fixing. The goal is to gain a deeper understanding of the legal implications of using indirect evidence within the procedural framework of Business Competition Law in Indonesia. To achieve this, a Normative Research method is employed, utilizing a multi-faceted approach. Through case analysis, statutory examination, conceptual exploration, and comparative study, the research explores patterns, legal frameworks, theoretical concepts, and perspectives from different jurisdictions, all related to the use of indirect evidence in the context of price fixing. The results revealed that Indirect evidence, classified as clue evidence under Perkom No. 1 Of 2019, encompasses communication and economic evidence. When direct evidence is lacking, these components, including documents or electronic information, play a crucial role in proving allegations of price-fixing. The legal implications of indirect evidence in the Indonesian competition law evidentiary system highlight its widespread use in resolving cases. However, there is a legal gap that poses challenges to the admissibility of indirect evidence in court proceedings. This emphasizes the need for legal reforms to effectively accommodate the role of indirect evidence.